The pleasures of crime : reading modern French crime fiction - Platten, David (Chiasma ;, 2011)
"For 150 years the French public and literati have enjoyed a love affair with crime fiction. This book investigates the nature of this relationship and how through periods of dramatic social and political change in France it has flourished. It challenges the conventional view of a popular genre feeding a niche market, depicting crime fiction instead as a field of creative endeavour, which has gradually matured into one of considerable literary fertility. By inviting us to share secrets and crack codes, creating suspense and (at times) not shirking from presenting horrific events in graphic language, the crime story brings into play the intellect and emotions of its readership. This book explores both this intrinsic literary value of the crime novel and its extrinsic witness to historical events and cultural trends, arguing that these apparently distinct aspects are in fact dynamic, interrelated parts of the same whole. This blend of cultural history with literary analysis allows for the discussion of themes such as politics, memory, the urban environment and youth cultures, mixed with case studies of major French crime writers, including Gaston Leroux, Georges Simenon, Jean-Patrick Manchette, Daniel Pennac and Fred Vargas."--Publisher's website.